1996
DOI: 10.1002/j.1552-4604.1996.tb04189.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Diurnal Variation in Glomerular Filtration Rates in the Elderly

Abstract: The present study was undertaken to examine the effect of age on diurnal variation in glomerular filtration rate (GFR). The GFR, as estimated by creatinine clearance (Clcr), was determined during a 24-hour period in 10 younger (mean +/- SD age 42 +/- 9 years) and 10 older (mean age 75 +/- 4 years) patients with hypertension. Significant diurnal variations in Clcr were observed in the younger patients, with a peak during the day and trough during the night. Such were not observed in the older patients, however.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This view is supported by the low agreement between the estimated and measured 24-hour creatininuria [16]. Circadian variability of GFR with lowered values during night-time may also be significant, although a previous study found this phenomenon somewhat blunted in the elderly when compared with younger subjects [17]. Therefore, the CINU obtained in the morning may not represent mean 24-hour GFR.…”
Section: Discussionmentioning
confidence: 66%
“…This view is supported by the low agreement between the estimated and measured 24-hour creatininuria [16]. Circadian variability of GFR with lowered values during night-time may also be significant, although a previous study found this phenomenon somewhat blunted in the elderly when compared with younger subjects [17]. Therefore, the CINU obtained in the morning may not represent mean 24-hour GFR.…”
Section: Discussionmentioning
confidence: 66%
“…The cellular origin and molecular mechanisms underlying the circadian rhythm of GFR have intrigued physiologists and clinicians for decades. Interest into this field was stimulated by clinical observations that the amplitude of circadian oscillations in GFR is reduced with age 35 and, that the circadian rhythm in GFR is dampened or inverted in patients with the nephrotic syndrome 14 , heart failure 36 or cirrhosis 12 . Early studies demonstrating that the circadian rhythm in GFR is independent on circadian oscillations in BP, cardiac output and sympathetic regulation suggested that an intrarenal self-autonomous mechanism(s) might be involved 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…If this variation of GFR over 24 h seems to be robust in young individuals, it might be blunted in older patients [10] or at least under particular conditions. Indeed, when compared with young hypertensive, older hypertensive subjects had blunted GFR oscillations as measured by creatinine clearance [11].…”
Section: Introductionmentioning
confidence: 95%